2020
DOI: 10.5812/amh.107878
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Resistin Levels and Diabetic Nephropathy in Type 2 Diabetic Patients

Abstract: Background: Resistin reduces tissue sensitivity to insulin and causes hyperglycemia. Diabetic nephropathy is also a metabolic disorder caused by chronic hyperglycemia that causes kidney dysfunction. Objectives: This study aimed to investigate the relationship between serum resistin and diabetic nephropathy in diabetic patients who referred to Imam Reza Hospital in 2018 - 2019. Methods: This case-control study recruited 30 diabetic patients with nephropathy, 29 non-nephropathy diabetic patients, and 30 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Researchers (44) further found that serum resistin levels in T2DM patients were positively correlated with Waist/Hip ratio, C-reactive protein, insulin resistance, and lipid profile, but negatively correlated with HDL-C. Pathogenesis of the polymorphism in the intron, +299 (G>A), is thought to affect gene expression and may contribute to increased resistin level as an inflammatory marker in subjects with DM (43). This parameter can be used as a biomarker for the severity of DM (45) One study conducted by Al Hilali showed there were statistically significant differences in fasting blood glucose, serum resistin, fasting insulin, insulin resistance as HOMA-IR and % HbA1C in the AA compared to the GA and GG genotypes of the T2DM group ( 41) and these results matched other studies (46) because the expression may be cis-regulated, meaning the presence of variations close to or in the RETN gene may affect the increase of mRNA transcription (47). Some associations were found between the RETN +299 (G/A) gene variation and insulin sensitivity in the T2DM group, and the HOMA index as an indicator of insulin resistance was significantly higher in subjects with AA and AA+GA genotypes compared to GG when compared to the controls.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers (44) further found that serum resistin levels in T2DM patients were positively correlated with Waist/Hip ratio, C-reactive protein, insulin resistance, and lipid profile, but negatively correlated with HDL-C. Pathogenesis of the polymorphism in the intron, +299 (G>A), is thought to affect gene expression and may contribute to increased resistin level as an inflammatory marker in subjects with DM (43). This parameter can be used as a biomarker for the severity of DM (45) One study conducted by Al Hilali showed there were statistically significant differences in fasting blood glucose, serum resistin, fasting insulin, insulin resistance as HOMA-IR and % HbA1C in the AA compared to the GA and GG genotypes of the T2DM group ( 41) and these results matched other studies (46) because the expression may be cis-regulated, meaning the presence of variations close to or in the RETN gene may affect the increase of mRNA transcription (47). Some associations were found between the RETN +299 (G/A) gene variation and insulin sensitivity in the T2DM group, and the HOMA index as an indicator of insulin resistance was significantly higher in subjects with AA and AA+GA genotypes compared to GG when compared to the controls.…”
Section: Discussionmentioning
confidence: 98%